Climate Change Mitigation and Flooding Governance: Recent Experience from Africa - SHIYANBADE, Bolanle Waliu; TALEAT, Bisiriyu Abiodun; AWODEJI, Mayowa Olaitan; ADEPOJU, Adewumi Sunday (Journal of Cultural Analysis and Social Change, 2026)
Across West and Sub-Saharan Africa countries, flood had claimed many lives and left thousands of people affected and loss of lives has been a notable consequence of flood. Evidences have shown that the recent flooding experience in some municipalities in African cities has become unbearable for the citizenry which has resulted to the impact of climate change on flooding emphasized on two major areas of livelihood, which are agriculture and health. Health risk is also attributable to climate-induced flooding as a result contaminated water due to destruction of crude oil and sewage pipelines and inadequate preparation for disaster. This paper relies heavily on secondary data as a method of gathering useful and important information as related to this study. The paper concluded that flood had continued to ravaged the state and the scourge of climate change had not been abated due to certain challenges militating against the implementation of the strategies in Africa.